Effect of laminated hydroxyapatite/gelatin nanocomposite scaffold structure on osteogenesis using unrestricted somatic stem cells in rat. (8th July 2013) - Tavakol, Shima; Azami, Mahmoud; Khoshzaban, Ahad; Ragerdi Kashani, Iraj; Tavakol, Behnaz; Hoveizi, Elham; Rezayat Sorkhabadi, Seyed Mahdi
Abstract Bone matrix consists of two major phases at the nanoscale: organic and hydroxyapatite. Nanotechnology as a diverse and interdisciplinary area of research has the capacity to revolutionise many areas of applications such as bone tissue engineering. Nanohydroxyapatite/gelatin composite has higher osteoblast attachment and proliferation than micro‐sized ones, and shorter culturing period and lower cell seeding density compared to pure gelatin. A nanostructured scaffold was fabricated by three methods for bone repair using nanohydroxyapatite and gelatin as the main components. Its biocompatibility, alizarin red test on the 14th and 21st days, gene expression on the 21st day in in vitro using and histomorphometry after 4 and 8 weeks post‐implantation in the rat were investigated. Cultured unrestricted somatic stem cells used for in vitro study showed an excellent level of cell attachment to the scaffold. Cells induced more osteoblast differentiation on the scaffold than in 2D cell culture. Osteoblast differentiation and bone regeneration results of in vitro and in vivo investigation on scaffold were extremely significant, better than control and treatment groups. These effects could be attributed to the shape and size of nanoHA particles and good architecture of the scaffold. The results confirm the feasibility of bone regeneration using synthesised scaffold as a temporary bone substitute.